The chapel of Pampulha and the church of águas, a possible relationship of brotherhood - de Avelar, Ana Paula Borghi; Toussaint, Michel; Da Cunha, João Alves (Seven Editora, 2023)
This article aims to analyze two Catholic temples of the 20th century, one Brazilian and one Portuguese. These are the Pampulha Chapel, the first modern Brazilian church, and the Igreja de Águas, the first church to be considered modern in Portugal. The Pampulha Chapel project is by the Brazilian architect Oscar Niemeyer and was inaugurated in 1943. The Igreja de Águas project, by the Portuguese architect Nuno Teotónio Pereira, was inaugurated in 1957. Beyond the great distance of the church’s inauguration date Brazilian for the Portuguese church, we can see points in common between them. Like the defense of modern religious architecture in their countries and a possible inspiration on the part of the Portuguese architect about modern Brazilian architecture. Relationships that we will discuss below. This article is part of a larger doctoral investigation, where the main focus is on proving a relationship between modern Brazilian religious architecture and modern Portuguese religious architecture. DOI: https://doi.org/10.56238/devopinterscie-065